2015
DOI: 10.1021/acs.jpca.5b08495
|View full text |Cite
|
Sign up to set email alerts
|

Vibrational Fingerprints of Low-Lying PtnP2n (n = 1–5) Cluster Structures from Global Optimization Based on Density Functional Theory Potential Energy Surfaces

Abstract: Vibrational fingerprints of small Pt n P 2n (n=1-5) clusters were computed from their low-lying structures located from a global exploration of their DFT potential energy surfaces with the GSAM code. Five DFT methods were assessed from the CCSD(T) wavenumbers of PtP 2 species and CCSD relative energies of Pt 2 P 4 structures. The eight first Pt n P 2n isomers found are reported. The vibrational computations reveal (i) the absence of clear signatures made by overtone or combination bands due to very weak mechan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…Indeed, considering only the four largest local a The atomic numbering follows the scheme depicted in Figure 4. contributions would cover 50% of the atomic motions, and can be easily interpreted as a rising of the molecule's extremes (atoms C 1 , C 2 , C 12 , and C 13 ) relative to the original plane of the molecule. On the other hand, the movement along the 48.8 cm −1 mode of helicene is described by VMARD using 13 internal coordinates.…”
Section: Comparison Between Ped and Vmardmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, considering only the four largest local a The atomic numbering follows the scheme depicted in Figure 4. contributions would cover 50% of the atomic motions, and can be easily interpreted as a rising of the molecule's extremes (atoms C 1 , C 2 , C 12 , and C 13 ) relative to the original plane of the molecule. On the other hand, the movement along the 48.8 cm −1 mode of helicene is described by VMARD using 13 internal coordinates.…”
Section: Comparison Between Ped and Vmardmentioning
confidence: 99%
“…The results displayed in Table 2 prompted the question of whether the use of additional (user-defined) internal coordinates would help describing these poorly localized modes. In the case of anthracene, two hypothesis were tested: in one case, we manually added the two torsions (τC (2) C ( 10) C ( 7) C (12) and τC (1) C ( 7) C ( 10) C ( 13) ), while in the second experiment two angle bendings were added (δC (2) C ( 10) C (13) and δC (1) C ( 7) C ( 12) ). The first case was mildly successful, with τC (1) C ( 7) C ( 10) C ( 13) achieving a weight of 15% in describing the atomic motions associated with the mode depicted in Figure 4a, with a corresponding decrease in the weights of the other internal coordinates listed in Table 2.…”
Section: Comparison Between Ped and Vmardmentioning
confidence: 99%
See 1 more Smart Citation
“…Computational studies have examined the molecular and electronic structures of bare Pt nanoclusters. Another study examined the molecular structure and vibrational features of platinum–phosphorus mixed clusters, Pt n P 2 n ( n = 1–5), using density functional theory (DFT) . Meanwhile, Huang and Lee used a cluster model approach to simulate the adsorption of CO on a Pt surface .…”
Section: Introductionmentioning
confidence: 99%
“… 13 15 Another study examined the molecular structure and vibrational features of platinum–phosphorus mixed clusters, Pt n P 2 n ( n = 1–5), using density functional theory (DFT). 16 Meanwhile, Huang and Lee used a cluster model approach to simulate the adsorption of CO on a Pt surface. 13 The study concluded that the size of the cluster impacts the adsorption of CO.…”
Section: Introductionmentioning
confidence: 99%